Clinical characterization and long-term outcome in children and adults with anti-AMPA receptor encephalitis - Milano, Chiara; Saylam, Ezgi; Papi, Claudia; Marmolejo, Laura; Sankovic, Alexandra; Reinecke, Raphael; Kerstens, Jeroen; Pizzanelli, Chiara; Simabukuro, Mateus Mistieri; Benaiteau, Marie; Joubert, Bastien; Gastaldi, Matteo; et al. (Neurology: Neuroimmunology & Neuroinflammation ; official journal of the American Academy of Neurology, 2025)
Background and Objectives - Anti-alpha-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid receptor (anti-AMPAR) encephalitis manifests as limbic encephalitis in adults and is often associated with cancer. Although some reports suggest that it may occur in children, the clinical features in this population, as well as the prognostic factors and long-term outcomes in children and adults, are unknown. - Methods - We performed a retrospective, international collaborative study of patients with anti-AMPAR encephalitis. Clinical information was reviewed, together with data from published pediatric patients. Clinical features of children and adults were compared with nonparametric tests. Survival rates (Kaplan-Meier curves) were compared using log-rank tests. Prognostic factors of poor outcome (modified Rankin Scale score >2) were identified using logistic regression models. - Results - A total of 115 patients were included, of whom 84 (71 adults, 13 children) had only AMPAR antibodies and 31 (27 adults, 4 children) had additional concurrent neural antibodies. Among patients with AMPAR antibodies alone, tumors were identified in 37 adults (56%) and none of the children (p < 0.0001). Children were more likely than adults to have behavioral/psychiatric symptoms (5/13, 39%, vs 8/71, 11%, p = 0.026) at onset, cerebellar dysfunction (6/13, 46%, vs 7/68, 10% p = 0.005) or movement disorders (5/13, 39%, vs 8/67, 12%, p = 0.032) during the disease course, and extratemporal brain MRI lesions (4/9, 44%, vs 5/44, 11%, p = 0.035). Among 34 patients with prolonged follow-up (>24 months), long-term neurocognitive sequelae were reported in 23 (68%), all adults. Failure to respond to first-line immunotherapy at multivariable analysis predicted a poor outcome (OR 8.0, 95% CI 1.1-59.2, p = 0.043). Among the 31 patients with concurrent neural autoantibodies, 22 (79%) had a tumor; those with high-risk antibodies had lower survival rates (p = 0.008). - Discussion - Children and adults with anti-AMPAR encephalitis show distinct clinical-radiologic features. At long-term follow-up, 68% of patients, all adults, have neurologic sequelae, with failure to respond to first-line immunotherapy being associated with worse outcomes.
Veröffentlicht: 18. Juli 2025
Gesehen am 28.11.2025